2018–2019 Florida Citrus Production Guide: Introduction - Lauren M. Diepenbrock; Megan M. Dewdney; Tripti Vashisth (EDIS, 2019)
This 4-page fact sheet is the introduction of the 2018–2019 Florida Citrus Production Guide. Written by L. M. Diepenbrock, M. M. Dewdney, and T. Vashisth, and published by the Plant Pathology Department, May 2018.